Macrostomia in association with pre-auricular tags: a case report - Andrade, Rodrigo Soares de; Machado, Renato Assis; Freitas, Edimilson Martins de; Martuscelli, Osiris José Dutra; Martelli, Daniella Reis B.; Coletta, Ricardo D.; Martelli-Júnior, Hercílio (Journal of Oral Diagnosis, 2016)
Macrostomia is a rare congenital anomaly with an incompletely described pathogenesis and several distinct non-syndromic phenotypes are associated. Macrostomia and pre- auricular tags usually can be correlated with syndromes, but in isolated cases are less common. Case report: In this case show a girl presenting macrostomia and pre-auricular tags isolated without association syndromic or other apparent causes. In the anamnesis, parents reported having a pregnancy without complications. In ectoscopic tests, ultrasound, and intra-oral physical examination were not significant alterations found beyond macrostomia and pre-auricular tags. It performed surgery to correct macrostomia and withdrawal of pre-auricular tags. Discussion: Macrostomia is a rare malformation that can only be treated surgically. Various surgical techniques have been described in the literature for the correction of these defects. In this case, the surgical option was the Z-plasty technique, however others techniques can be chosen according to the position of facial cleft. Conclusion: Although rare in occurrence, requires further studies to a better knowledge leading to a more effective diagnosis and treatment of the patient.